Towards sustainable production and consumption: A novel DEcision-Support Framework IntegRating Economic, Environmental and Social Sustainability (DESIRES). (4th August 2016) - Azapagic, Adisa; Stamford, Laurence; Youds, Lorraine; Barteczko-Hibbert, Christian
Graphical abstract: Outline of the DESIRES framework. Highlights: A novel framework for sustainability assessment (DESIRES) has been developed. DESIRES integrate economic, environmental and social sustainability. It comprises a suite of tools such as LCA, LCC, SLCA, system optimisation and MADA. Application is illustrated by a case study related to a future electricity supply. Abstract: The idea of sustainable production and consumption is becoming a widely-accepted societal goal worldwide. However, its implementation is slow and the world continues to speed down an unsustainable path. One of the difficulties is the sheer complexity of production and consumption systems that would need to be re-engineered in a more sustainable way as well as the number of sustainability constraints that have to be considered and satisfied simultaneously. This paper argues that bringing about sustainable production and consumption requires a systems approach underpinned by life cycle thinking as well as an integration of economic, environmental and social aspects. In an attempt to aid this process, a novel decision-support framework DESIRES has been developed comprising a suite of tools, including scenario analysis, life cycle costing, life cycle assessment, social sustainability assessment, system optimisation and multi-attribute decision analysis. An application of the framework is illustrated by a case study related to energy.